“Varii errores qui ab origine mundi emerserunt”. The semantic scope of the term “heresy” in Philastrius’ of Brescia Diversarum hereseon liber - Szram, Mariusz (Vox Patrum, 2018)
The bishop of Brescia, Philastrius, author of the first Latin catalogue of heresies, written between 380 and 388, presented in his treaty an extremely large number of heterodox movements: 28 within Judaism and 128 in early Christianity. This comes as a result of a wide understanding of the term heresis. For Philastrius this term was synonymous with the term error, recognized as any deviation from the universal truth in the history of the world, inspired by Satan as “the father of lies”, ocurring primarily in Judaism and Christianity. Among the early Christian views defined by the bishop of Brescia as heresy five groups can be distinguished. The first group includes mainly the erroneous views on fundamental theological questions contained in the rule of faith, such as the concept of a creator God and saviour Jesus Christ. The second set of heresies, closely related with the previous one, contains the erroneous doctrines of anthropology, such as questioning the resurrection of the human body or the view of the materiality of the human soul. The third group includes the views related to the misinterpretation of Scripture, especially exaggerated literal interpretations of the texts of the Old Testament, as well as the cosmological views which do not agree with descriptions contained within the Bible. The fourth group contains the moral issues related to the based on laxism or rigorism way of life, as well as to the attitude of lack of deference to the laws of the Church, but non-threatening the primary truths of the Christian faith. The fifth group of heresies includes the movements defined by the authors of the late patristic period as a schizm, while the term schisma is not at all used by the bishop of Brescia in his work. The semantic scope of the term heresis in Philastrius’ treaty went beyond the noncompliance with the regula fidei. According to the bishop of Brescia each offense – whether in doctrinal teaching or practice of life, as well as with regard to the understanding of the text of Scripture – is a heresy because it offends God and the Church. Therefore, in Philastrius opinion one should not differentiate between superior and minor error, but equally condemn them as attitudes directed against God as the Father of Truth.